Acquired idiopathic phlebectasia of the penis: case report - Houry, Younes; Labyad, Abdessamad; Redouan, Rabii (International Surgery Journal, 2020)
There is a many example of diseases of blood vessels involving serious diagnostic difficulties and sometimes the etiologic factors may be only presumed. Varicose veins rarely affect the penis, and we were unable to find in dermatologic and urologic literature reports of a similar case. We report here a case of a 26-year-old man with a history of a penis getting bigger since his adolescent life associated with minor pain, discomfort, and a primitive erectile dysfunction. After a complete medical history, physical examination and ultrasonic doppler color investigation, the diagnosis of acquired phlebectasia of the penis was confirmed. The patient was treated surgically by ligaturing and section of the voluminous dorsal varicose veins of the penis and reducing the ventral scrotal skin, with successful aesthetic and functional results, with a follow up more than 3 months. Varicose veins of the penis are an exceptional pathology. This condition may not need any treatment. However, when varicose veins cause great discomfort, pain, aesthetic or sexual issues, surgery is the best option of the patient.